2019
DOI: 10.2106/jbjs.19.00776
|View full text |Cite
|
Sign up to set email alerts
|

Work Relative Value Units Do Not Adequately Support the Burden of Infection Management in Revision Knee Arthroplasty

Abstract: Background: Revision total knee arthroplasty for infection is challenging. Septic revisions, whether 1-stage or 2-stage, may require more time and effort than comparable aseptic revisions. However, the burden of infection may not be reflected by the relative value units (RVUs) assigned to septic revision compared with aseptic revision. The purposes of this study were to compare the RVUs of aseptic and septic revision total knee arthroplasties and to calculate the RVU per minute for work effort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…However, it is unclear whether reimbursement algorithms consider the higher resource utilization, complexity, and operative time associated with the burden of infection management with rTHA-I. Although multiple studies exploring revision total knee arthroplasties have demonstrated inadequate compensation for those due to infection 41-44 , there remains minimal information regarding whether this disparity is found for rTHA procedures. Our analysis demonstrated a consistent devaluation of both types of rTHA procedures over the past 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether reimbursement algorithms consider the higher resource utilization, complexity, and operative time associated with the burden of infection management with rTHA-I. Although multiple studies exploring revision total knee arthroplasties have demonstrated inadequate compensation for those due to infection 41-44 , there remains minimal information regarding whether this disparity is found for rTHA procedures. Our analysis demonstrated a consistent devaluation of both types of rTHA procedures over the past 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, calculating the surgeon's work only based on the length of a surgical operation causes bias. It may be necessary for a patient to consult a surgeon before surgery, or to be followed up with a surgeon for a long time after surgery in some cases (9). In contrast to measuring operation times, this study suggests considering pre-and post-operative care times as well.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Prior studies in the orthopedic literature have compared reimbursement for specific Current Procedural Terminology (CPT) codes and found that typically longer and more complex procedures are not appropriately compensated when compared to shorter ones. [9][10][11][12][13][14] Understanding reimbursement patterns is the first step in identifying any mismatches between reimbursement and work performed for categories of procedures to help direct policy changes by subspecialty organizations. Understanding these patterns also better enables orthopedists to advocate for fair compensation for a given procedure.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 Prior studies in the orthopedic literature have compared reimbursement for specific Current Procedural Terminology (CPT) codes and found that typically longer and more complex procedures are not appropriately compensated when compared to shorter ones. 9 , 10 , 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%